Kinetic inhibition performance of N-vinyl caprolactam/isopropylacrylamide copolymers on methane hydrate formation. (1st March 2022) - Long, Zhen; Zhou, Xuebing; Lu, Zhilin; Liang, Deqing
Abstract: Low dosage kinetic hydrate inhibitors play an important role in flow assurance for oil and gas industry. New polymers especially based on N-vinyl caprolactam (NVCap) are widely designed to serve as potential inhibitors. In this work, a series of random copolymers of NVCap with hydrophobic monomer isopropylacrylamide (NIPAM) were synthesized. The effect of molecular weight on inhibition performance of newly copolymers (PVCap-co-NIPAM)s on CH4 hydrate formation were firstly examined and compared with N-vinyl caprolactam homopolymer (PVCap). The macroscopic kinetic tests indicated that all the copolymers were more powerful than PVCap as nucleation inhibitors under the same conditions. Significant reductions in the hydrate growth rates by 1.0 wt% inhibitors were also observed. Copolymers with the lowest molecular weight possessed the best suppression performance. Powder X-ray diffraction and Raman spectra indicated neither PVCap nor PVCap-co-NIPAM affected the hydrate structure due to their too large molecular size to match the hydrate cages. However, cage-dependent gas occupancy calculated from Raman data proved that the polymers preferred to hinder CH4 molecules from being trapped by large cages (5 1, 2 6 2 ). A possible inhibition mechanism of PVCap-co-NIPAM was also proposed. These results could be helpful to develop synergistic kinetic hydrate inhibitors for guaranteeing pipeline fluids transportation safety. Graphical abstract: Image 1 Highlights: Copolymers of N -vinyl caprolactam and isopropylacrylamide were firstly synthesized. Introducing isopropylacrylamide yielded a synergetic kinetic inhibitory effect. The copolymer with lower molecular weight exhibited better inhibition performance. PXRD patterns showed the copolymer was too large to change hydrate microstructure. The inhibition mechanism based on macroscopic and Raman measurements was proposed.